Strategi Optimalisasi Peran Perbankan Syariah terhadap Industri Fashion Halal di Kabupaten Cirebon - M.Sopyan Fadillah; Ika Rarawahyuni; Adi Indradi Wazdi (Masoem University, 2023)
The purpose of this study was to determine the role and achievement of working capital financing bank BSI KCP. Plered to the halal fashion industry through SWOT analysis and optimize the strategies applied in optimizing the role of Islamic banking to the halal fashion industry. The method used is Mix method. This study was conducted by collecting data from interviews and questionnaires with a population of 10 samples, using primary and secondary data that can strengthen the research. Then perform the processing of data obtained by the SWOT Matrix and internal-external Matrix. From the results obtained is the role of bank BSI KCP. Plered against the halal fashion industry as a facilitator in strengthening business capital by providing working capital financing products. But the achievement of bank BSI KCP. Plered against the financing of 30% per month of November from the allocation of 20% of the overall financing. Of course, this is still not optimal in performing its role. Then when viewed from internal and external factors that the bank BSI KCP. Plered is in a very advantageous position, because it has the power and opportunities that can be utilized to the maximum. Further position of the company bank BSI KCP. Plered is in Quadrant I means that it can use aggressive strategies by using factors of Strenght-Opportunity (S-O) as a strategy to optimize and implement its business.